Pengaruh beberapa Jenis Media Tanam terhadap Produksi Bunga Petunia Grandiflora (Petunia grandiflora Juss.) dalam Sistem Soilless Culture - Ilham Fairuz Tirta Aji; Nugraheni Widyawati (Universitas Sebelas Maret, 2019)
Nowadays urban and rural communities have an interest in choosing a place to live or a comfortable and fresh environment. The purpose of this research was to study the type of planting media other than soil that can support flowering of petunia plants. The research was conducted in Salaran experimental field, Satya Wacana Christian University, Wates Village, Getasan District, Semarang Regency from August-October 2018. The research used Randomized Block Design with 6 treatment and 4 replications. Media types were: P1 (rockwool), P2 (raw husk), P3 (charcoal husk), P4 (bricks), P5 (cocopeat) and P6 (zeolite). Parameters considered include plants, number of leaves, number of productive branches, stem diameter and number of flowers. Data were analyzed using Variant Analysis (ANOVA) followed by Honestly Significant Difference Test with 95% confidence interval adn correlation test. This research showed that zeolite growing media was able to support flowering of petunia plants with the highest average number of flowers (6.17) followed by brick planting media (5.38). Productivity of petunia per plant is closely related to plant height, number of leaves, productive branches, but not closely related to stem diameter.